Strategi Salahuddin Al-Ayyubi dalam Mempersatukan Dunia Muslim Di Tengah Tekanan Perang Salib - Nurannisa (Tumanurung: Jurnal Sejarah dan Budaya, 2025)
This research aims to explain the strategies of Salahuddin Al Ayyubi in uniting the Muslim world amidst the pressure of the Crusades. This research uses historical research consisting of heuristics, source criticism, interpretation and historiography. This approach uses religious, political, and social approaches. The results of this research reveal that Salahuddin Al Ayyubi’s strategy in uniting Muslims was by uniting Muslim forces which lead to the conquest of cities like Amid, Syria, Aleppo, Acre, Asqalan and various other cities. Additionally, Salahuddin built positive relationships with other Muslim rulers, namely the Abbasid Dynasty, to secure support from the Caliphate. He also suppressed the Shia movement in Egypt, Syria, and Yemen, as it posed a threat to Islamic unity. After unifying Egypt and Sham under his rule, Salahuddin Al-Ayyubi focused his attention on attacking the Christian Europe and successfully defeated the Crusader forces captured the city of Jerusalem in 1187 AD.